Bone Marrow Derived Myeloid Cells Orchestrate Antiangiogenic Resistance in Glioblastoma through Coordinated Molecular Networks - Achyut, B.R. (Cancer Lett, 2015)
Glioblastoma (GBM) is a hypervascular and malignant form of brain tumors. Anti-angiogenic therapies (AAT) were used as an adjuvant against VEGF-VEGFR pathway to normalize blood vessels in clinical and preclinical studies, which resulted into marked hypoxia and recruited bone marrow derived cells (BMDCs) to the tumor microenvironment (TME). In vivo animal models to track BMDCs and investigate molecular mechanisms in AAT resistance are rare. We exploited recently established chimeric mouse to develop orthotopic U251 tumor, which uses as low as 5×10(6) GFP+ BM cells in athymic nude mice and engrafted >70% GFP+ cells within 14 days. Our unpublished data and published studies have indicated the involvement of immunosuppressive myeloid cells in therapeutic resistance in glioma. Similarly, in the present study, vatalanib significantly increased CD68+ myeloid cells, and CD133+, CD34+ and Tie2+ endothelial cell signatures. Therefore, we tested inhibition of CSF1R+ myeloid cells using GW2580 that reduced tumor growth by decreasing myeloid (Gr1+ CD11b+ and F4/80+) and angiogenic (CD202b+ and VEGFR2+) cell signatures in TME. CSF1R blockade significantly decreased inflammatory, proangiogenic and immunosuppressive molecular signatures compared to vehicle, vatalanib or combination. TCK1 or CXCL7, a potent chemoattractant and activator of neutrophils, was observed as most significantly decreased cytokine in CSF1R blockade. ERK MAPK pathway was involved in cytokine network regulation. In conclusion, present study confirmed the contribution of myeloid cells in GBM development and therapeutic resistance using chimeric mouse model. We identified novel molecular networks including CXCL7 chemokine as a promising target for future studies. Nonetheless, survival studies are required to assess the beneficial effect of CSF1R blockade.